Contribution Margin and Popularity Analysis for Top Ten Menus in the X Restaurant Bogor - Agung Gita Subakti (Binus Business Review, 2011)
One of the growing tourism facilities is the restaurant that offers a certain menu. Can be ascertained with the development of restaurants in the city of Bogor and the race in competition provides satisfaction to its customers are increasing. Although customer satisfaction is one of the main goals, but there is another side that often burdens the mind of the restaurant. The burden of thought is simply presented in the following question: why is the menu that is sold in demand does not provide a significant profit, but the menu that is sold less in demand has made significant profit. One of the efforts made to face the fact this is the menu still serves as a typical restaurant menu, even though profits are not significant. On the other principle that the sale should provide benefits can still be significant, so to overcome this problem required steps up marketing strategies and design with attention to any changes that occurred.